Pregnancy Outcomes in HIV-Infected Women: Experience from a Tertiary Care Center in India - Vatsla Dadhwal, MD; Aparna Sharma, MD; Kavita Khoiwal, MD; Dipika Deka, MD; Plaboni Sarkar, MD; P. Vanamail, MPS, PhD (Global Health and Education Projects, Inc., 2017)
Background and Objectives: There is conflicting data on the effect of HIV infection as well as antiretroviral therapy (ART) on pregnancy outcome. The objectives of this study were to compare pregnancy outcomes in women with and without HIV infection, and to evaluate the effect of HAART on pregnancy in HIV-infected women. Methods: This is a prospective case record analysis of 212 HIV-infected women delivering between 2002 and 2015, in a tertiary health care center in India. The pregnancy outcome in HIV-infected women was compared to 238 HIV-uninfected controls. Women received ART for prevention of mother to child transmission as per protocol which varied during the period of study. Effect of use of ART on preterm birth (PTB) and intrauterine growth restriction (IUGR) was analyzed. Results: HIV-infected women were more likely to have PTB, IUGR, and anemia (9.4%, 9.9%, 5.2%) compared to uninfected women (7.6%, 5%, 3.8%), this did not reach statistical significance (P-value = >0.05). The incidence of PIH, diabetes mellitus and intrahepatic cholestasis of pregnancy was similar in both groups. Mean birth weight was significantly lower in neonates of HIV-infected women (2593.60±499g) than HIV-uninfected women (2919±459g) [P-value=0.001]. neonatal intensive care unit admissions were also significantly higher in infants born to HIV-infected women (P-value=0.002). HIV-infected women on ART had decreased incidence of PTB and IUGR. Conclusion and Global Health Implications: Good antenatal care and multidisciplinary team approach can optimize pregnancy outcomes in HIV-infected women. Key words: Human Immunodeficiency Virus • Preterm Birth • Intrauterine Growth Restriction • Antiretroviral Therapy Copyright © 2017 Dadhwal et al.This is an open-access article distributed under the terms of the Creative Com-mons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.